Rabies and other lyssavirus diseases. - Warrell, M; Warrell, D (2004)
The full scale of the global burden of human rabies is unknown, owing to inadequate surveillance of this fatal disease. However, the terror of hydrophobia, a cardinal symptom of rabies encephalitis, is suffered by tens of thousands of people each year. The recent discovery of enzootic European bat lyssavirus infection in the UK is indicative of our expanding awareness of the Lyssavirus genus. The main mammalian vector species vary geographically, so the health problems created by the lyssaviruses and their management differ throughout the world. The methods by which these neurotropic viruses hijack neurophysiological mechanisms while evading immune surveillance is beginning to be unravelled by, for example, studies of molecular motor transport systems. Meanwhile, enormous challenges remain in the control of animal rabies and the provision of accessible, appropriate human prophylaxis worldwide.